Accuracy of Diffusion-weighted Magnetic Resonance Imaging in Detecting Mucosal Healing and Treatment Response, and in Predicting Surgery, in Crohn's Disease. (9th July 2018) - Thierry, Marie-Lise; Rousseau, Hélène; Pouillon, Lieven; Girard-Gavanier, Mélanie; Baumann, Cédric; Lopez, Anthony; Danese, Silvio; Laurent, Valérie; Peyrin-Biroulet, Laurent
Abstract: Background and Aims: The Nancy score is a luminal Crohn's disease [CD] activity index applied in diffusion-weighted magnetic resonance imaging [DW-MRI]. We assessed the accuracy of the Nancy score in detecting mucosal healing and treatment response, and in predicting surgery. Methods: This was a retrospective, single-centre study of all patients with active CD and serial DW-MRI before and after treatment initiation with a biologic drug, between January 2010 and September 2016. The gold standard was endoscopy. The association between the Nancy score and the cumulative probability of intestinal resection during follow-up was tested combining Kaplan-Meier curves and log-rank testing. Results: A total of 96 patients were included; 20 had concomitantly undergone endoscopy. The Nancy score correlated well with the Crohn's Disease Endoscopic Index of Severity [r = 0.60 for the total score and r = 0.63 for the segmental score]. A total Nancy score <6 and a segmental Nancy score <2 detected mucosal healing with an area under the receiver operating characteristic curve [AUROC] of 0.82 (95% confidence interval [CI] 0.69–0.94, p <0.0001) and 0.80 [95% CI 0.73–0.87, p <0.0001], respectively. The Nancy score was highly sensitive to changes [Guyatt's responsiveness indices: 1.18 for the total score and 0.85 for the segmental score]. Mucosal healing on DW-MRI after treatment initiation was associated with a lower cumulative probability of intestinal surgery ( p = 0.0251, median [interquartile range: IQR] follow-up 2.2 [1.6–3.7] years). Conclusions: In CD, the Nancy score accurately detects mucosal healing and treatment response, the latter associated with a lower likelihood of intestinal resection.